1998
DOI: 10.1063/1.121945
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy study of Si nanowires

Abstract: Microstructures of Si nanowires ͑SiNW's͒ synthesized using laser ablation were investigated by transmission electron microscopy. The SiNW's have a high density of structural defects, which may play an important role in the formation of SiNW's and in the determination of the morphology of the nanowires. A model for the growth mechanism of the SiNW's was discussed on the basis of the observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 12 publications
1
38
0
1
Order By: Relevance
“…Nevertheless most of the wire still keeps the [115] growth direction according to the EDP and the highresolution images. In the present study it is very interesting to ®nd that [115] orienta- , Zhou et al 1998, Holmes et al 2000 may also directly connect through (111) twinning, as seen schematically in ®gures 5 (d) and (e). Since the lattice orientation in a wire can provide a tuning parameter to adjust physical properties, a speci®c curved and heavily twinned silicon nanowire may have proper-464 X. L. Ma et al ties that are di erent from others among the huge number of nanowires, a selection of which is shown in ®gure 1.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless most of the wire still keeps the [115] growth direction according to the EDP and the highresolution images. In the present study it is very interesting to ®nd that [115] orienta- , Zhou et al 1998, Holmes et al 2000 may also directly connect through (111) twinning, as seen schematically in ®gures 5 (d) and (e). Since the lattice orientation in a wire can provide a tuning parameter to adjust physical properties, a speci®c curved and heavily twinned silicon nanowire may have proper-464 X. L. Ma et al ties that are di erent from others among the huge number of nanowires, a selection of which is shown in ®gure 1.…”
mentioning
confidence: 88%
“…It is frequently assumed that a single silicon nanowire has a unique crystallographic or growth orientation along the wire axis. Most silicon nanowires have been reported to have growth orientations of h112i , Zhou et al 1998) and h111i (Morales and Lieber 1998, Tang et al 1999, although other growth orientations, such as [100] and [113], are also observed occasionally (Tsutsumi et al 1999, Kamins et al 2001, Ko et al 2001. However, silicon nanowires, particularly for those grown by thermal evaporation and laser ablation, are commonly highly curved in morphology and heavily twinned in microstructure.…”
mentioning
confidence: 97%
“…66 Similar experiments were performed by other groups, [67][68][69] and a typical example of Si nanowires obtained by laser ablation is shown in Figure 7b. Peng et al 69 investigated the influence of temperature, Zhang et al 70 the influence of ambient gas, and Zhou et al 71 the crystallography of the nanowires. As an alternative to Fe, also Ni, 72 Pr, 73 and Ru 73 were successfully tested as catalyst metals.…”
Section: Laser Ablationmentioning
confidence: 99%
“…[12][13][14] Here, the SiNWs were synthesized in a tube furnace by the oxide-assisted ͑OAG͒ method. 12,15 SiO powder source was placed at the center zone of the furnace where the temperature was 1200°C.…”
mentioning
confidence: 99%